For rent. - Lim, Xin Hui. (2009)
For Rent is a video documentary produced by a group of students from the Wee Kim Wee School of Communication and Information (WKWSCI) at the Nanyang Technological University (NTU) in Singapore as part of their Final Year Project (FYP). It invites viewers on a journey to uncover the secrets of residing in subsidized HDB one/two room rental flats in many parts of Singapore. Through the accounts of the residents, it attempts to paint a clearer picture of the lives and challenges that this often-forgotten community faces.